2017
DOI: 10.1016/j.arth.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Fretting and Corrosion Between a Metal Shell and Metal Liner May Explain the High Rate of Failure of R3 Modular Metal-on-Metal Hips

Abstract: The high failure rate of the metal liner option of the R3 acetabular system may be attributed to corrosion on the backside of the liner which appear to result from geometry and design characteristics of the acetabular shell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…[7][8][9] Retrieval analysis studies of acetabular components have reported similar findings. 1,2,[10][11][12] However, a recently published in vitro study has found that MACC may not be a significant driver of taper corrosion in titanium shell-CoCrMo liner acetabular tapers, 13 especially when compared with head-neck tapers with the same material combination.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Retrieval analysis studies of acetabular components have reported similar findings. 1,2,[10][11][12] However, a recently published in vitro study has found that MACC may not be a significant driver of taper corrosion in titanium shell-CoCrMo liner acetabular tapers, 13 especially when compared with head-neck tapers with the same material combination.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the modularity of modern revision systems, the number of interfaces increases, and therefore it is reasonable to assume that the chance for particle debris is amplified. Adverse reactions to metal debris (ARMD) and corrosion increase as the number of interfaces increases and have been described for modular revision implants in numerous previous studies [27][28][29][30]. Interestingly, while the amount of relative movement between the shell and the cup increased for both groups, the S-group started with a significantly higher amount of relative movement and remained higher throughout all load levels when compared to the nS-group.…”
Section: Discussionmentioning
confidence: 82%
“…The benefits of using an acetabular liner within a shell include ease of revision by changing the liner without removing a well‐integrated acetabular cup. In addition, shell fixation with screws is required in cases of bone tissue loss, and a modular acetabular component allows for this possibility without interfering with the bearing surface of the femoral component . The early designs comprised of non‐cross‐linked ultra‐high molecular weight polyethylene (UHMWPE).…”
Section: Introductionmentioning
confidence: 99%
“…Recent retrieval studies have shown that modular acetabular components, primarily associated with MoM designs, sustain damage in their taper junctions, usually attributed to mechanically‐assisted crevice corrosion (MACC) and wear . However, the nature of the damage observed in these tapers is distinctly different than that seen in, for example, head‐neck junctions.…”
Section: Introductionmentioning
confidence: 99%